2013
DOI: 10.1111/cas.12159
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin Nup188 is required for chromosome alignment in mitosis

Abstract: Most cancer cells are aneuploid, which could be caused by defects in chromosome segregation machinery. Nucleoporins (Nup) are components of the nuclear pore complex, which is essential for nuclear transport during interphase, but several nucleoporins are also known to be involved in chromosome segregation. Here we report a novel function of Nup188, one of the nucleoporins regulating chromosome segregation. Nup188 localizes to spindle poles during mitosis, through the C‐terminal region of Nup188. In Nup188‐depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…S4). To test whether CLIP-170 phosphorylation on T287 might play a role in KT-MT attachment, we examined the stability of K-fibers during cold treatment using an approach described previously (Itoh et al, 2011;Itoh et al, 2013). Immunofluorescence data showed that cells expressing mCherry-CLIP-170-T287A had unstable K-fibers and unattached chromosomes, whereas cells expressing mCherry-CLIP-170-WT had robust and stable K-fibers after cold treatment (Fig.…”
Section: Plk1 Recruitment To Kinetochores Is Dependent On Cdk1 Phosphmentioning
confidence: 99%
See 2 more Smart Citations
“…S4). To test whether CLIP-170 phosphorylation on T287 might play a role in KT-MT attachment, we examined the stability of K-fibers during cold treatment using an approach described previously (Itoh et al, 2011;Itoh et al, 2013). Immunofluorescence data showed that cells expressing mCherry-CLIP-170-T287A had unstable K-fibers and unattached chromosomes, whereas cells expressing mCherry-CLIP-170-WT had robust and stable K-fibers after cold treatment (Fig.…”
Section: Plk1 Recruitment To Kinetochores Is Dependent On Cdk1 Phosphmentioning
confidence: 99%
“…The primary antibodies were detected by using Alexa-Fluor-labeled secondary antibodies at a dilution of 1:500 (Molecular Probes), and DNA was counterstained with 1 mg/ml DAPI. Analyses of cold-stable microtubules were performed as reported previously (Itoh et al, 2011;Itoh et al, 2013).…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, forced dimerization of Nup62 perturbs the directional trafficking of cytosolic proteins into the cilium, but has no effect on membrane proteins (Takao et al, 2014). Studies by other groups have shown functional roles for the nucleoporins Nup62 and Nup188 at the centrosome, which contributes its mother centriole to form the ciliary basal body (Hashizume et al, 2013;Itoh et al, 2013). Tantalizing evidence that RanGTP localizes to the axoneme and that nuclear import factor importin-β2 (also known as transportin 1) is required to import multiple ciliary proteins is consistent with the hypothesis that nucleoporins at the cilium might regulate directional transport of proteins into and out of the ciliary matrix, in addition to functioning as a general diffusion barrier (Dishinger et al, 2010;Hurd et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of a mutant form of Nup98, which cannot be phosphorylated by the Nek kinases, stabilizes the NPC and delays mitotic entry (Laurell et al, 2011). Noting that several NPC components have now been reported to localize to the base of the cilium or to the centrosome (Hashizume et al, 2013;Itoh et al, 2013;Kee et al, 2012), we hypothesized that Nup98 plays a role in the integrity of the cilium downstream of Nek2, similar to the way it plays a role in the integrity of the NE.…”
Section: Introductionmentioning
confidence: 98%